Beyond fur color: differences in socio-emotional behavior and the oxytocin system between male BL6 and CD1 mice in adolescence and adulthood - Katharina Gryksa; Theresa Schäfer; Franziska Gareis; Elena Fuchs; Melanie Royer; Anna K. Schmidtner; Anna Bludau; Inga D. Neumann (Frontiers in Neuroscience)
IntroductionThe development of stress-related psychopathologies, often associated with socio-emotional dysfunctions, is crucially determined by genetic and environmental factors, which shape the individual vulnerability or resilience to stress. Especially early adolescence is considered a vulnerable time for the development of psychopathologies. Various mouse strains are known to age-dependently differ in social, emotional, and endocrine stress responses based on genetic and epigenetic differences. This highlights the importance of the qualified selection of an adequate strain and age for any biomedical research. Neuropeptides like oxytocin (OXT) can contribute to individual and strain-dependent differences in emotional and social behaviors.MethodsIn this study, we compared anxiety- and fear-related, as well as social behavior and pain perception between male adolescent and adult mice of two commonly used strains, C57BL/6N (BL6) and CD1.ResultsWe revealed BL6 mice as being more anxious, less social, and more susceptible toward non-social and social trauma, both in adolescence and adulthood. Furthermore, during development from adolescence toward adulthood, BL6 mice lack the reduction in fear- and anxiety-related behavior seen in adult CD1 mice and show even higher social fear-responses and perception of noxious stimuli during adulthood. Analysis of the OXT system, by means of receptor autoradiography and immunohistochemistry, showed strain- and age-specific differences in OXT receptor (OXTR) binding in relevant brain regions, but no differences in the number of hypothalamic OXT neurons. However, intracerebroventricular infusion of OXT did neither reduce the high level of anxiety-related nor of social fear-related behavior in adult BL6 mice.DiscussionIn summary, we show that male BL6 mice present an anxious and stress vulnerable phenotype in adolescence, which further exacerbates in adulthood, whereas CD1 mice show a more resilient socio-emotional state both in adolescence as well as during adulthood. These consistent behavioral differences between the two strains might only be partly mediated by differences in the OXT system but highlight the influence of early-life environment on socio-emotional behavior.